"Caracterización de consorcios microbianos con capacidad biorremediadora de pesticidas piretroides (Cipermetrina), organofoforados (Clorpurifos) y N-(fosfonometil) glicina (GLIFOSATO)" - Morrillo Zambrano, Pablo Andrés (2018)
The objective of the research is to isolate and characterize the biological bed microbial consortium (Biodep) with bioremediation capacity of pyrethroids (cypermethrin), organophosphorus (chlorpyrifos) and N-phosphonomethyl glycine (glyphosate). The importance is focused on the high rates of pesticides used for the phytopatological problems that afflict the agricultural sector. Agricultural use of pesticides is a subset of the broader spectrum of chemicals used in modern society. Bioremediation uses the ability of microorganisms to degrade organic compounds. This technology is based on the use of natural or genetically enhanced organisms to recover contaminated sites and protect the environment. Bioremediation practices consist mainly of the use of different organisms (plants, yeasts, fungi, bacteria, etc.) of the medium to neutralize toxic substances, either by transforming them into less toxic substances or by rendering them harmless to the environment and Human health. These decontamination systems are based on the absorption of organic substances by these microorganisms, which use them as the source of carbon necessary for their growth and energy for their metabolic functions. For the selection of the microbial strain, the growth of all the microorganisms isolated in solid mineral culture medium with addition of 0.5% of pesticide will be carried out, developmental and adaptability dimensions will be evaluated at 2 and 6 days after inoculation in medium of culture. Key words: Biostimulation, Biodegradation, microbial characterization, biological cycle, BPH, culture medium, pesticides, Pseudomonas.